Unsteady Flow Separation and High Performance of Airfoil with Local Flexible Structure at Low Reynolds Number (Communications in Computational Physics, 2014)
The unsteady flow separation of airfoil with a local flexible structure (LFS)is studied numerically in Lagrangian frames in detail, in order to investigate the natureof its high aerodynamic performance. For such aeroelastic system, the characteristic-based split (CBS) scheme combined with arbitrary Lagrangian-Eulerian (ALE) framework is developed firstly for the numerical analysis of unsteady flow, and Galerkinmethod is used to approach the flexible structure. The local flexible skin of airfoil,which can lead to self-induced oscillations, is considered as unsteady perturbation tothe flow. Then, the ensuing high aerodynamic performances and complex unsteadyflow separation at low Reynolds number are studied by Lagrangian coherent structures (LCSs). The results show that the LFS has a significant influence on the unsteadyflow separation, which is the key point for the lift enhancement. Specifically, the oscillations of the LFS can induce the generations of moving separation and vortex, whichcan enhance the kinetic energy transport from main flow to the boundary layer. Theresults could give a deep understanding of the dynamics in unsteady flow separation andflow control for the flow over airfoil.